Pengaruh Terapi Bermain Dengan Media Capit Dan Pom-Pom Terhadap Kemampuan Mengenal Warna Pada Anak Tunagrahita Ringan Kelas IV Di SLB Marsudi Putra 1: indonesia - Atikah Putri Shidqiyah; Dwi Setianingsih (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
The effect of the play therapy method using claws and pom-poms media with claws and pom-poms media on the ability to recognize color in class IV mild mentally retarded children at Marsudi Putra 1 SLB. This research was conducted at Marsudi Putra 1 SLB from April 2023 to May 2023. This study aims to determine the effect of the Play Therapy method with tweezers and pom-poms on the ability to recognize color in children with mild mental retardation, a type of research that uses a quantitative approach with a pre-designed -Experimental. The type used is (One Group Pretest-Posttest Design) because in this study it compared conditions before and after being given treatment. This situation was measured using tests related to the ability to recognize colors after being given treatment using claw and pom-pom media. In conducting data collection is done by pre-test and post-test. Based on the results of the research that has been done, it was found that there was an increase in the ability to recognize colors, thus it can be concluded that the play therapy method with tweezers and pom-pom media had an effect.